A Study Of The Effectiveness Implementation Of Total Quality Management And Just-In-Time In Telekom Billing Operation - Omar, Shahnim (2000)
This dissertation is a study of the effectiveness implementation of total quality management(TQM) and just-in-time (JIT) billing in Telekom billing operation. It is based on the exiting billing operation that has been continuosly improved since beginning